A New Non-iterative Method for Pressure-driven Snapshot Simulations with EPANET. (2017) - Pacchin, E.; Alvisi, S.; Franchini, M.
Abstract: This study compares different recently proposed methods for Pressure-Driven snapshot simulations of water distribution networks using the EPANET software interface and proposes a new one. The proposed method is based on the insertion of a sequence of devices consisting of a General Purpose Valve (GPV), a fictitious junction, a reach with a check valve and a reservoir at each water demand node. The proposed method differs from other methods previously proposed in the literature – and similarly based on the insertion of sequences of devices consisting of a valve and a reservoir or emitter – in that it uses a GPV. In fact the GPV allows the user to define the relationship between the flow (i.e. supplied demand) and available pressure, making the proposed sequence of devices capable of representing different relationships among these variables, unlike the other non-iterative methods already proposed in the scientific literature, in which the relationship is implicitly fixed by the structure of the sequence of devices used. Applications to two case studies and comparison with the results of the non-iterative methods already proposed in the scientific literature highlight the accuracy and flexibility of the proposed method and show, by contrast, the unreliability and limits, in terms of precision, of some of the methods previously proposed in the literature.